Clinical radiological and pathological assessment of benign breast lumps: our institutional experience - Bangaru, Himabindu; Chandra, Alluru Sarath; Gaiki, Varun Vijay (International Surgery Journal, 2017)
Background: With increased awareness about breast cancer, many women with breast lumps are attending clinics. Though benign breast lumps are most common, they may be associated with morbidity and have become cause for concern to patients. Triple assessment by clinical, radiological and pathological examination is a standard approach in the evaluation of breast lumps. Even in cases of benign breast diseases, multimodality tests are being preferred to give reassurance to patients. This study was aimed to study distribution of various benign breast lumps in relation to age at presentation, to identify sensitivity and specificity of clinical breast examination, Ultrasonography (USG) and Fine needle aspiration cytology (FNAC) methods in the evaluation of benign breast lumps and to compare with final histopathological diagnosis. Methods: A retrospective study was conducted in department of general surgery at Malla Reddy institute of medical sciences, Hyderabad from August 2013 to July 2017. 202 females with benign breast lumps were evaluated by clinical breast examination, ultrasonography (USG) and Fine needle aspiration cytology (FNAC) methods. All patients underwent excision biopsy of lump. Final histopathological report was taken as reference standard. Results: Fibroadenoma was most common in 2nd decade. Clinical breast examination and USG showed good sensitivity but less specificity than FNAC. FNAC showed both good sensitivity and specificity. There was very good degree of agreement between FNAC and histopathological diagnosis (Kappa=0.911). Conclusions: Good clinical examination can give accurate preoperative diagnosis of benign breast lumps. Triple assessment by clinical breast examination, USG and FNAC can be useful in the evaluation of benign breast lumps.